Charge of the lightning bugs - Cummings, Troy (Cummings, Troy. Notebook of doom, 2015)
It is the first day of the brand-new Stermont Elementary School, but everything electrical seems to be going haywire, and it looks like strange green lightning bugs are draining off the power--but when they see green lightning in a clear blue sky Alexander and his friends know there must be a monster involved.